Electrical safety in low voltage distribution systems up to 1 000 V AC and 1 500 V DC. Equipment for testing, measuring or monitoring of protective measures. Non-contact AC voltage indicators (IEC 61557-17:2021) Part 17, (18th May 2022) - British Standards Institution,
No abstract available